Evaluation of the impact of Covid-19 on basic education in Mexico and Colombia - Villa-Guardiola, Vera Judith; Romero-González, Zilath; Hernández-Ramírez , Sandra Lucero (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The present article evaluates the situation of basic education in the republics of Mexico and Colombia, as a result of the health emergency caused by the Covid-19. The research was developed through the analytical-synthetic method, under the holistic research paradigm, which allowed the understanding of the phenomenon studied through data analysis and comparison techniques and instruments. Inequalities in access to education are observed in both countries, caused in particular by the lack of knowledge of the use of new technologies by students and teachers. The foregoing becomes a limitation of progress, of social changes and the cause of a greater distancing from the expected social justice, making it impossible to perceive, disseminate and respect human rights and provide high quality education to new generations of citizens.